The fall of the Seleukid empire 187-75 B.C. - Grainger, John D., 1939-, (Pen & Sowrd Military, 2015)
"The concluding part of John D Grainger's history of the Seleukids traces the tumultuous last century of their empire. The Seleukid dynasty (founded by one of Alexander the Great's generals) ruled an empire which at one time was the largest state on earth. Although it was still a major power following the defeat by the Romans at Magnesia, in the ensuing period their realm was riven by dynastic disputes, secession and rebellion, the religiously inspired insurrection of the Jewish Maccabees, civil war and external invasion from Egypt in the West and the Parthians in the East. By the 80s BC, the empire was disintegrating, internally fractured and squeezed by the expansionist powers of Rome and Parthia. This is a fittingly dramatic and colourful conclusion to John Grainger's masterful account of this once-mighty empire, whose decline and eventual extinction reshaped the ancient world."--Book jacket.